Tinjauan Konsep Maslahah dan Mafsadah Pernikahan Disabilitas Dalam Perspektif Hukum Keluarga Islam - Bin Aly Yahya, Achmad (Cv. Kalimasada Group, 2025)
Marriage is one of the religious orders and also the only way to channel the desires of a person's biological needs that are permitted by religion. Seen from this point of view, then when someone gets married at that time he does not only have the desire to fulfill his biological needs which by nature must be channeled. People with disabilities, both in institutions and outside institutions, have basic rights that must be fulfilled and protected. These basic rights include criminal and citizen rights. Citizen rights include the ability to make employment contracts and get married. The possibility of the desire of people with mental disabilities to get married remains. This study aims to analyze the legal status of marriage of people with disabilities from the perspective of Islamic family law and evaluate its validity based on the pillars and conditions of marriage. In addition, this study also aims to examine the marriage through the approach of the concept of maslahah and mafsadah to see its positive and negative impacts on the household life of people with disabilities. This type of research is qualitative research with a normative approach (normative juridical), namely examining primary and secondary legal materials related to Islamic family law and marriage of people with disabilities. The marriage process carried out by people with disabilities is valid as long as it fulfills the pillars of marriage while still having to adjust to the type of disability inherent in both bride and groom. So that a solution can be found for the process or implementation of the ijab qobul which is the core of the marriage process, either by words, writing or gestures. In marriage of people with disabilities, there are various considerations between the decision to marry or not. Marriage of disabilities is a consideration based on whether there is maslahah or not. In this case, the clear maslahah is to protect a person with disabilities from committing adultery, while on the other hand, there are still doubts about their ability to live a household life.